FECUNDITY OF A COBITID FISH LEPIDOCEPHALUS GUNTEA (HAMILTON) - DAS, KASTURI; DASGUPTA, M. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2009)
Fecundity of Lepidocephalus guntea belonging to Nadia district of West Bengal was estimated. It ranged from 550 to 9615.714 in total body length measuring 8.2.to 9.5 cm and total weight ranging from 4.150 to 8.100 g, respectively. The average fecundity was determined to be 4852.512. Number of eggs per gm body weight and number of eggs per cm body length was found to be average 816.508 eggs/gm and 557.183 egg/cm, respectively. The relationship between fecundity and total body length, total weight, ovary weight and also between ovary weight and total length have been determined. The different results obtained were analyzed statistically.